Write and Let Go: An Online Writing Program for University Students - Batista, João; Marinai, Janine C.; Gouveia, Melissa; Oliveira, João Tiago; Gonçalves, Miguel M. (Frontiers in Psychology, 2022)
Background: There are a plethora of studies on expressive writing and positive writing interventions, but few have addressed the combination of both paradigms. Additionally, research on the role of ambivalence towards change in the context of writing-based interventions is scarce. Ambivalence towards change is a natural movement of approaching and avoiding change that may occur in various situations. In psychotherapy, its resolution is associated with successful outcomes. Aim: In this study, we tested a combination of expressive and positive writing paradigms in an internet-based intervention for university students. By focusing participants on a current, unresolved problem, it was also possible to study the role of ambivalence towards change in writing interventions. Methods: We recruited 172 participants who were randomly divided into experimental (n= 85) and control (n= 87) groups. The intervention consisted of the identification of a present problem and four writing tasks on consecutive days. Assessment was conducted at baseline, posttest on both groups and follow-up in the experimental group. Participants in the experimental condition were also assessed after each task. Measures of anxiety, depression, rumination, ambivalence, distress and well-being (optimism, affect and satisfaction with life) were collected. Results: Multivariate analysis of variance (MANOVA) showed that participants in the experimental group had a significant decrease from baseline to posttest in ambivalence and rumination when compared with the control group. These changes were maintained at follow-up. No differences were found in the remaining measures. A decrease in ambivalence, rumination and distress was also found throughout the intervention in the experimental group. Discussion: Considering different perspectives about a current difficulty and using a combination of expressive and positive writing fostered the reduction of ambivalence towards change and rumination. Ambivalence reduction after the second writing task may have created optimal conditions for the subsequent decrease in rumination and distress. Future studies should replicate this finding and dismantle the components that are more adequate in changing these variables.